Vizslas - Duling, Kaitlyn (Minneapolis, MN : Bellwether Media, 2020)
Relevant images match informative text in this introduction to Vizslas. Intended for students in kindergarten through third grade.
Includes bibliographical references (page 23) and index.
1.9
K-3
530L
L
Keywords: Vizsla -- Juvenile literature; Vizsla; Dogs; Readers (Elementary)